Tinjauan Metode Gamifikasi dalam Menyelesaikan Konflik Pertemanan Yang Terjadi Pada Gen Z - Isnaeni Safina Nur Aulia; Rosa Karnita (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2025)
Communication among friends in Generation Z often leads to conflicts caused by differences of opinion, personal feelings, and a lack of understanding of interpersonal relationships. These factors can affect the quality of communication within a friendship. This study aims to understand how conflicts arise within Generation Z friendships. The conflicts identified are addressed by examining gamification methods through interactive media as a tool for self-reflection in resolving friendship issues among Generation Z. Gamification methods have the potential to serve as an engaging and relevant learning medium, thereby offering a strategic solution to enhance empathy and the quality of interpersonal communication among Generation Z. A qualitative approach was employed in this study through data collection via a literature review of previous research, a survey of 61 participants, and in-depth interviews with 2 individuals. The interviews were conducted by considering different perspectives regarding friendship conflicts among Generation Z. The results of the data analysis indicate that Generation Z frequently experiences friendship conflicts caused by jealousy, differences of opinion, and a lack of understanding regarding the Feeling of the conversation partner and interpersonal communication. Further research is recommended to test the effectiveness of gamification media through experimental methods in measuring improvements in empathy and communication by developing a more specific game design model based on interpersonal communication theory and social psychology.